Empirical Explication of Psychological Space Sovereignty in Indicators of Personality Social Self-Control - Havryliuk, Irina (Psychological Prospects Journal, 2019)
The article represents the results of theoretical and empirical study of psychological space sovereignty in the features of social self-control of student youth. The theoretical grounding of the problem concerns the determination issues of psychological space sovereignty, its structural components and effective characteristics of autonomy and success of behavior. It is emphasized that sovereignty of psychological space is condition and result of adaptability, maturity and productivity of personality and interaction success of individuality and society depends on the qualitative characteristics of the formed social self-control of personality. The specification of interrelation between the psychological space sovereignty definition and the social self-control of student youth makes it possible to consider the ability to exercise control over own behavior as indicator of social and psychological adaptation, which compacts the limits of psychological space. The developed program of empirical research, as well as the complex of the used methods of mathematical statistics of the results, allow to specify the theoretical positions in the form of real psychological facts: students with the formed sovereignty of psychological space (high and average level) are more «principled», and hence their orientation on internal experiences in social interaction allows unobstructedly to overcome the negative moments of social and psychological adaptation, and their expressive stability of behavior defines the greater coherence of emotional support of interpersonal interaction; students with unformed sovereignty of psychological space (low level), demonstrate «pragmatism», which blocks the development of adequate system of social self-control, and is expressed in anxiety of social usefulness in interpersonal interaction.